Thursday
March 23, 2017

Post a New Question

Posted by on Monday, May 7, 2012 at 9:39pm.

rewrite the quadratic equation y=-3x^2+3x+2 into standard form to determine the vertex

--------, ---------, --------

  • ALGEBRA 2 - , Tuesday, May 8, 2012 at 5:02am

    y = -3(x^2 - x + 1/4) + 2 + 3/4
    y = -3(x - 1/2)^2 + 11/4
    (y - 11/4) = -3(x - 1/2)^2

    now just read off the vertex

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question